Pentahelix Approach in Community Empowerment-Based Ecotourism: Turtle Conservation and Waste Management on Santen Island Beach, Banyuwangi - Jayanti Dian Eka Sari; Aditya Yudhana; Melati Octavia Febriana; Syahrul Novenda Ramadhanny; Firrial Eksa Maulidania Putri; Suhainizam Bin Muhamad Saliluddin; Ratih Novita Praja (Knowledge Dynamics, 2024)
Background: Santen Island Beach, Banyuwangi, faces significant challenges from waste mismanagement and its impact on marine ecosystems, particularly the endangered sea turtles. This study addresses these issues through a community empowerment program grounded in the Pentahelix framework, engaging stakeholders from government, academia, businesses, communities, and media. The program, active since 2022, aims to integrate sustainable waste management and turtle conservation into community development. Methods: The study employed a community empowerment approach, incorporating waste segregation, educational tourism initiatives, and turtle conservation training. Collaborations with local organizations like the Banyuwangi Sea Turtle Foundation and waste management entities ensured resource and expertise mobilization. Activities included waste alms programs and sea turtle egg relocation to sandless hatching boxes, supplemented by training and social media campaigns. Results: The program achieved key milestones, such as forming empowered cadres for waste management and turtle conservation, introducing effective waste segregation practices, and increasing hatchling survival rates through innovative relocation techniques. Outputs included community-led eco-tourism branding, scientific and media publications, and economic benefits for local stakeholders. Conclusion: This initiative highlights the potential of integrating environmental conservation and economic empowerment within a sustainable development framework. By leveraging the Pentahelix model, the program fosters local ownership and long-term impact, addressing SDG goals related to responsible consumption and marine ecosystem preservation. Continued efforts, such as enhancing cadre competencies and optimizing ecotourism branding, are recommended for sustained outcomes.